Mutations in CCDC39 and CCDC40 are the Major Cause of Primary Ciliary Dyskinesia with Axonemal Disorganization and Absent Inner Dynein Arms. Issue 3 (11th February 2013) - Antony, Dinu; Becker‐Heck, Anita; Zariwala, Maimoona A.; Schmidts, Miriam; Onoufriadis, Alexandros; Forouhan, Mitra; Wilson, Robert; Taylor‐Cox, Theresa; Dewar, Ann; Jackson, Claire; Goggin, Patricia; Loges, Niki T.; et al.
<x xml:space="preserve">Abstract</x> Around 12% of patients with primary ciliary dyskinesia (PCD), a recessively inherited ciliopathy caused by cilia/sperm dysmotility, have perturbed 9+2 microtubule cilia structure and inner dynein arm (IDA) loss. We find that biallelic CCDC39 and CCDC40 mutations cause 69% of this defect (37/54 families). We report 25 (19 novel) mutant alleles all causing predicted "null" alleles, with 73% homozygous mutations (27/37 families) including a major putative hotspot mutation, CCDC40 c.248delC. We propose the renaming this disorder to "IDA and microtubular disorganisation defect". <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>